Presence of biogas from food wastes: a preliminary study / Salmi Nur Ain ... [et al.] - Nur Ain, Salmi; Sukor, Mohd Zaki; Jehan Elham, Omar Syah; Noraini, Masila
The accumulation of solid organic waste is thought to be reaching critical level in almost all regions of the world including Malaysia. These organic wastes need to be managed in a sustainable way to avoid depletion of natural resources, minimize risk to human health, reduce environmental burdens and maintain an overall balance in the ecosystem. There are numbers of method currently being applied to the treatment and management of solid organic waste. One of the methods is anaerobic digestion. Anaerobic digestion is a biological process in which the microorganisms will break down biodegradable material in the absence of oxygen yielding the product biogas. Food waste with high content of carbon can be considered as a good source of substrate to produce biogas via fermentation process. In this research, the digestion of food waste (FW) and sludge water (SW) was used. The experiment was conducted in the digester model with different ratio of SW and FW. The digester model was filled with different ratio of SW to FW by mass. The ratio are 1:1, 1:3, 1:5, and one model which acts as a control. The amount of biogas collected was observed every 5 days. From the observation, it shows that the amount of biogas collected and the production rate with ratio 1:5 is higher as compared to the other model. From the observation, it can be predicted that the production rate of biogas can be increased when it has large amount of food waste with a large number of carbon content. From the result obtained, it shows that the food wastes have the potential in producing biogas.